Upaya Meningkatkan Sikap Cinta Tanah Air Melalui Permainan Tradisional Egrang - Mustofa Azis, Rasyaf; Ahmad Fauzi, Rizal; Rukmana, Anin (Universitas Hamzanwadi, 2024)
The problem is how learning outcomes, student activities, implementation, and planning increase the love for traditional egrang games. The purpose of the study was to examine how learning outcomes, student activities, implementation, and planning plans increase a sense of love for traditional egrang games. The method used in this research is class action research. The number of subjects was 25 people with 14 boys and 11 girls. This study uses a selfreport instrument in the form of a questionnaire, IPKG, and egrang learning test format. pre-cycle observation results get a total score of 1540 (12%). In cycle I action, the total score was 1670 (40%). When compared to the results of the pre-cycle observation assessment, cycle I action has increased by 28%. In the second cycle action, the total score was 1940 (88%). In the third cycle action, the total score was 2170 (100%). When compared to cycle II action, cycle III action has increased by 12%. Thus, the results of the research action data are considered to have reached the target. It can be concluded that the process of classroom action research (PTK) on efforts to increase love through traditional egrang games can be categorized that this research is successful. This is evidenced by the design of planning and implementation of actions that pay close attention to the components related to the research.